Cells - Boyd, Kyle; Angel, Charlotte; Cambridge Educational (New Jersey : Cambridge Educational, 2005)
Takes a close-up look at the common denominator of all life, the cell. It illustrates essential cellular processes, which is transportation of materials, communication, energy transfer, protein-building, waste disposal, movement, and the all-important mitosis and meosis as well as key cellular landsmarks like the nucleus, ribosomes, mitochondria, the Golgi complex, the endoplasmic reticulum, and lysosomes
Title from title screen
Narrator: Jason Watt
Keywords: Cells; Cytology; Cell physiology